Possible new γ-ray pulsar detections by the AGILE and GLAST missions: An outer gap model look at the Parkes pulsar catalog - Torres, D.F. (2003)
Fil:Torres, D.F. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.